Translating the DCFR and drafting the CESL : a pragmatic perspective - Pasa, Barbara; Morra, Lucia (Sellier European Law Publishers, 2014)
Translating the DCFR and writing the CESL have been extremely complex enterprises, and closely dependent one on the other. The volume takes a pragmatic approach in describing them. Structured in four parts, it sets out the historical and philosophical background of legal translation, and then focuses more narrowly on the legal translation processes adopted in the DCFR and the CESL.